Motivasi Berwirausaha Dalam Perspektif Peran Pendidikan dan Lingkungan Keluarga Pada Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan Tahun 2013 - Kristinawati, Kristinawati; , Drs. Sami'an, M.M (2017)
The purpose of this research are: (1) To determine how much influence the role of education to increase the motivation are self-employed (2) To determine how much influence the environment of family to increase the motivation are self-employed (3) To determine how much the role of education and the environment of family on increasing the motivation are self-employed on the student of accounting education force 2013. The type of research is quantitative escriptive. The population in this study are students of Muhammadiyah University of Surakarta in accounting education force in 2013 who took a course of ntrepreneurial practices in the 5th semester, amounting to 92 students with a sample of 72 students were taken by proportional random sampling lottery.Data collection techniques by using questionnaires that have been tested by validity and reliability testing and documentation methods. The data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination, the effective contribution and relative contribution. The conclusion that can be drawn from this study are: 1) There is significant influence between the role of education on entrepreneurship motivation by t test derived from the value of tcount> t table is 2.161> 1.995 with significance probability value <0.05, namely 0.034 and effective contribution (SE ) amounted to 6,39%. 2) There was a significant effect of family environment on ntrepreneurship motivation by t test obtained by value tcount>t table is 4.399 > 1.995 with a significant probability value <0.05, namely 0.000 and effective contribution (SE) of 22.01%. 3) There is significant influence between education and the role of family environment on entrepreneurship motivation berdasrkan F test known Fhitung> Ftable is 13.656> 1.836 and significant probability value <0.05 is 0.000 with a coefficient of determination (R2) of 28,4% while the remaining 71,6% is influenced by other variables outside of this study. Keywords: the role of education, family environment, entrepreneurship motivation.